2023
DOI: 10.3390/biology12040583
|View full text |Cite
|
Sign up to set email alerts
|

Amplectobeluid Radiodont Guanshancaris gen. nov. from the Lower Cambrian (Stage 4) Guanshan Lagerstätte of South China: Biostratigraphic and Paleobiogeographic Implications

Abstract: Radiodonta, an extinct stem-euarthropod group, has been considered as the largest predator of Cambrian marine ecosystems. As one of the radiodont-bearing Konservat-Lagerstätten, the Guanshan biota (South China, Cambrian Stage 4) has yielded a diverse assemblage of soft-bodied and biomineralized taxa that are exclusive to this exceptional deposit. “Anomalocaris” kunmingensis, the most abundant radiodont in the Guanshan biota, was originally assigned to Anomalocaris within the Anomalocarididae. Despite this taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Amplectobelua symbrachiata has been described from the Niutitang Formation (Cambrian Stage 3-South China) (Steiner et al, 2005). The Guanshan Biota (Cambrian Stage 4-South China) is the only locality in which we find Guanshancaris kunmingensis (previously called "Anomalocaris" kunmingensis) (Wang et al, 2013;Zeng et al, 2018;Jiao et al, 2021;Zhang et al, 2023). The Latham Shale, also Stage 4 (Laurentia), has yielded Ramskoeldia cf.…”
Section: Amplectobeluidaementioning
confidence: 50%
See 3 more Smart Citations
“…Amplectobelua symbrachiata has been described from the Niutitang Formation (Cambrian Stage 3-South China) (Steiner et al, 2005). The Guanshan Biota (Cambrian Stage 4-South China) is the only locality in which we find Guanshancaris kunmingensis (previously called "Anomalocaris" kunmingensis) (Wang et al, 2013;Zeng et al, 2018;Jiao et al, 2021;Zhang et al, 2023). The Latham Shale, also Stage 4 (Laurentia), has yielded Ramskoeldia cf.…”
Section: Amplectobeluidaementioning
confidence: 50%
“…Computational modelling has shown that such motions are not possible with Anomalocaris appendages (De Vivo et al, 2021), nor was their sclerotised cuticle capable of tearing a mineralised exoskeleton (Bicknell et al, 2023). Damages preserved in trilobite and nektaspid exoskeletons (Conway Morris, 1985;Nedin, 1999) and large coprolites found in Cambrian lagerstätten that contain fragments of trilobites (Nedin, 1999;Vannier and Chen, 2005) had previously been attributed to durophagous predation by radiodonts (Nedin, 1999;Klug et al, 2017;Vinn, 2018;Zong, 2021;Zhang et al, 2023). Based on the unsuitability of the frontal appendage (De Vivo et al, 2021;Bicknell et al, 2023) and oral cone (Daley and Bergström, 2012) for durophagy, Anomalocarididae are no longer considered to have been predators of mineralized shelly taxa, and instead these coprolites and damages are attributed to Redlichia and other Cambrian trilobites (Daley et al, 2013b) or gnathobase-bearing artiopodan euarthropods (Bicknell et al, 2018;2022).…”
Section: Feeding Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Many radiodonts possess frontal appendages that are considered to have been raptorial and able to capture, manipulate and perhaps even masticate prey, before passing food items to the mouth for further processing [ 6 , 17 22 ]. In this context, select radiodonts are hypothesized to have been capable of shell-crushing (durophagous) predation [ 21 23 ], but there is still uncertainty as to whether breaking biomineralized prey was achievable using the frontal appendages, paired gnathobase-like structures affiliated with segments transitional between the head and trunk, the oral cone, or a combination of these, depending on the taxon [ 5 , 6 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%